Analisis Pengaruh Pengumuman Earning terhadap Abnormal Return dan Tingkat Likuiditas Saham: Analisis Empiris pada Nonsynchronous Trading - Indah Kurniawati (Jurnal Akuntansi dan Auditing Indonesia, 2006)
The objective of this study is to examine the effect of the earnings information on market reaction in the Jakarta Stock Exchange. The sample consists of 34 stocks of firms from 2003 - 2004. The hypothesis was tested by market model (Brown and Warner, 1985) and correcting the beta bias made use of Fowler and Rorke Method (1983) with four lags and four leads. The signifi¬cance of the difference of market reactions was tested by Wilcoxon Signed Ranks test. The result of this research shows that earning announcements is positively responded statistically but not significantly by the market around the date of earning announcement. The dif¬ference between stock liquidity before and after the earning announcement is insignificant except trading volume.Keywords: earning, market reaction, stock liquidity